2015
DOI: 10.1038/ncomms8025
|View full text |Cite
|
Sign up to set email alerts
|

A mechanistic model of tau amyloid aggregation based on direct observation of oligomers

Abstract: Protein aggregation plays a key role in neurodegenerative disease, giving rise to small oligomers that may become cytotoxic to cells. The fundamental microscopic reactions taking place during aggregation, and their rate constants, have been difficult to determine due to lack of suitable methods to identify and follow the low concentration of oligomers over time. Here we use single-molecule fluorescence to study the aggregation of the repeat domain of tau (K18), and two mutant forms linked with familial frontot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
210
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 183 publications
(234 citation statements)
references
References 43 publications
18
210
0
Order By: Relevance
“…The predicted numbers of aggregates are large, in the order of 10 4 species per cell-like volume, values that correspond to micromolar concentrations of the aggregates, requiring multiple species to enter this volume at the same time. These requirements for the templated seeding of αS are relatively high in comparison with, for example, recently reported results for tau K18 using a similar approach (26). It is interesting to note that our kinetic analysis can be used to predict some of the conditions when a small number of oligomers or fibrils may be effective at seeding the aggregation reaction, and hence templated seeding might readily occur.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The predicted numbers of aggregates are large, in the order of 10 4 species per cell-like volume, values that correspond to micromolar concentrations of the aggregates, requiring multiple species to enter this volume at the same time. These requirements for the templated seeding of αS are relatively high in comparison with, for example, recently reported results for tau K18 using a similar approach (26). It is interesting to note that our kinetic analysis can be used to predict some of the conditions when a small number of oligomers or fibrils may be effective at seeding the aggregation reaction, and hence templated seeding might readily occur.…”
Section: Discussionmentioning
confidence: 55%
“…To date, evidence has been obtained about the mechanism of αS aggregation in solution (20)(21)(22) and in the presence of lipid membranes that are thought to play an important role in vivo (23)(24)(25). Single-molecule studies combined with detailed kinetic analysis have provided us with an opportunity to define the sequence of events during the aggregation process in great detail (26)(27)(28). Our related studies using single-molecule fluorescence techniques to follow the aggregation of αS identified a slow conversion step from the initially formed, proteinase (endopeptidase) K-sensitive oligomers to more compact, proteinase K-resistant oligomers.…”
Section: Significancementioning
confidence: 99%
“…To overcome this problem, we have developed an array of single‐molecule techniques11, 12, 13, 14 to observe oligomeric species individually, and have applied them to characterise the aggregation pathway of several disease‐related proteins in vitro. In many such methodologies, the protein of interest needs to be tagged with either an organic fluorophore or a fluorescent protein.…”
mentioning
confidence: 99%
“…Recent intensive research into the physicochemical properties of amyloid and its formation into fibrils in the citoplasm points attention to growth models [3], [29], [38], [31]. In [39] the authors consider the growth of aminoid fibrils and look for a mechanistic explanation of the process in terms of a biochemical reaction network.…”
Section: Fibrillationmentioning
confidence: 99%
“…Let M be the total amount (concentration) of monomer, F be the fibril and C = M -F be the monomer-fibril complex at the time t of aggregation [3], [29], [38], [39]. After aggregation the complex C turns into fibril F , that is, the added monomer molecule M converts into (part of) the fibril F .…”
Section: A a Basic Verhulst-henri Modelmentioning
confidence: 99%